Advanced surface finishing of aerospace materials using magnetic media - Ng, Yong Rui (2015)
As 3D printing or additive manufacturing becomes more prominent, the techniques required in finishing components produced through that method also gain importance. Additive manufacturing is already being utilised to create engine and turbine parts in the aerospace industry. Hence, it is crucial to find ways to implement finishing techniques similar to MAF in the aerospace industry. The aim of this study is to conduct a capability study of a novel internal surface finishing technique using magnetic tool with flexible shaft. The finishing process was designed and its experimental setup was assembled. A factorial experiment was conducted to investigate the effects of the internal magnetic finishing on surface roughness and material removal by varying the current, vibration frequency and the abrasive grit number. The process was employed on SS316 and Ti-6Al-4V workpieces. From the results, it is observed that the finishing technique was able to polish the internal surfaces of both SS316 and Ti-6Al-4V workpieces. Even though interaction effects were found between the three process variables, the main effects were dominant. This is true for both SS316 and Ti-6Al-4V workpieces. The most dominant factor was found to be grit number. Higher grit number causes an increase in material removal. Higher current causes an increase in material removal. Higher vibration frequency leads to an increase in material removal. In addition, it was found out that on smooth surfaces (Ra<1µm), lower current results in smoother finished surface. In conclusion, it can be determined that the internal magnetic finishing technique is a plausible method to polish SS316 and Ti-6Al-4V internal surfaces. Further research needs to be done to analyse its accessibility and applicability for more complex internal geometries.